Dosimetric Comparison of Lung-Sparing Radiation Therapy between Volumetric Arc Therapy and Helical Tomotherapy for Unresectable Malignant Pleural Mesothelioma. (21st December 2019) - Pehlivan, Berrin; Sengul, Kansu; Yesil, Abdullah; Nalbant, Nilgul; Ozturk, Osman; Ozdemir, Yurday; Topkan, Erkan
Abstract : Objective . To compare volumetric arc therapy (VMAT) and helical tomotherapy (HT) plans in terms of dosimetric parameters in positron emission tomography- (PET-) computerized tomography- (CT-) based radiation therapy planning in unresectable malignant pleural mesothelioma (MPM). Methods . CT and coregistered PET-CT data from seven patients with histologically-proven MPM were utilized for VMAT and HT plans. Target volumes and organs at risk (OARs) were delineated. The prescription doses for planning target volume 1 (PTV1 ) and PTV2 were 45.0 Gy and 54 Gy in 1.8 Gy/fr, respectively. Each technique was evaluated in terms of target volume coverage and OAR doses. Findings . Although the maximum (p = 0.001 ) and mean (p < 0.001 ) doses of PTV1, and PTV2 (p < 0.001 for maximum and p = 0.001 for mean doses) favored the HT technique over VMAT, both techniques efficiently covered the target volumes. Additionally, HT also provided more homogeneous dose distribution (p < 0.001 ) and numerically lower doses received by most OARs, but again both rotational techniques were successful in keeping the OAR doses below the universally accepted limits. The major disadvantage of the HT technique was the requirement for longer treatment times (7.4 versus 2.5 minutes/fr; p < 0.001 ) to accomplish the intended treatment. Conclusion . Results of this dosimetric comparison clearly demonstrated the possibility of safe hemithoracic irradiation of medically/technically unresectable MPM patients with either of the two rotational RT techniques, namely the VMAT and HT. Clinically, considering their poor prognosis, these promising findings may open a potential new window for curative treatment of unresectable MPM patients, if further confirmed by future clinical studies.